Classic Type I-IV Hypersensitivity Reactions in the Skin (Out of Print) - Pranav Sheth; Edmund Choi; Karen Marsh; Kyle Sliney; Adam Schirmer (Association of American Medical Colleges, 2009)
Abstract Introduction Hypersensitivity reactions have traditionally been divided into four types: type I, II, III, and IV. These reactions may involve one or more organ systems and have varied clinical presentations. This tutorial introduces the user to the prototypical clinical presentation of the type I through IV reactions as they occur in the skin. Methods Animation of the proposed mechanism of each type of reaction is presented in each section. The clinical morphology of the reaction in the skin, as well as a brief differential diagnosis of the clinical presentation and histopathology, are reviewed. Case studies, guide questions, and interactive histologic identification give students a chance to assess their own understanding. Results In a recent evaluation of the module by second-year medical students (N = 27), 91% felt it was valuable to work through the guide questions throughout the module and 65% felt that the questions helped them to be more active learners. Overall response was very positive. Discussion This work is unique in that it bridges the gap between immunology and clinical dermatology using animation, photos, diagrams, and interactive histology assessments.